Comparison of the Effect and Durability of Lumbar Stabilization and Global Postural Reeducation Exercises on Movement Control, Pain and Disability in Men with Lumbar Movement Control Dysfunction - Abolfazl Rahmani (Zabol University of Medical sciences, 2021)
Introduction: The global postural reeducation (GPR) method seems to be an effective method for the treatment of musculoskeletal disorders; therefore, the aim of this study was to compare the effect and durability of 6 weeks of GPR and lumbar stability exercises on movement control, pain and disability in men with chronic nonspecific low back pain (NSLBP) with lumbar movement control dysfunction.Methods: Based on the inclusion and exclusion criteria, 46 men with non-specific chronic low back pain (LBP) with lumbar movement control dysfunction were selected and randomly divided into three groups (two exercise groups - one control group). Training intervention groups practiced for six weeks, three sessions per week. Visual analogue scale (VAS), Roland Morris questionnaire, and movement control test were used to measure pain, level of physical disability, and lumbar movement control, respectively. Repeated measures ANOVA was utilized to compare the effect and durability of the two training protocols on the dependent variables at a significant level.Results: Results from this research showed that both types of exercises reduced pain (P = 0.001) and improved disability index (P = 0.001) and lumbar movement control (P = 0.001). Our findings suggested that a GPR intervention for 6 weeks (P = 0.040) and inactivity for 4 weeks (P = 0.001) resulted in a greater improvement in disability compared to the lumbar stabilization exercises (LSEs). Conclusion: Both types of exercises seem to be effective in improving lumbar movement control, pain, and disability in people with movement control dysfunction after both training and inactivity. The GPR method improved disability more than the LSEs.